Metabolismo de vitamina C em acerola (malpighia emarginata dc): estudo da expressão gênica e atividade enzimática - Pereira, João Alves Ferreira (2021)
Acerola is a fruit recognized for its high content of vitamin C (vit. C), a compound with high antioxidant potential, used in the most diverse reactions to control cellular homeostasis, reducing damage from oxidative stress, in addition to other functions. The content of vit. C in vegetables is related to the stage of development, therefore, this study aims to characterize physically and chemically the stages of development of acerola, focusing mainly on the enzymatic and molecular metabolism of vitamin C. The experiment started with the marking of flowers in anthesis and then the fruits were harvested throughout their development and evaluated in terms of physical, physico-chemical analyzes to study the physiology during the development and ripening of the '‘Flor-branca’' acerola, as a way of identifying the appropriate harvest stages for different post-harvest uses. In a second experiment, '‘Flor-branca’' acerola fruits were harvested at five developmental stages (based on the stages defined in the first experiment), evaluated for vit content. C, activity of enzymes related to biosynthesis, degradation and recycling, and analysis of gene expression related to vit metabolism. C in real time (RT-qPCR). The data obtained from the study were submitted to analysis of variance and Tukey's test at 5% probability. The results of experiment 1 highlight that during the '‘Flor-branca’' development from anthesis to full maturation it takes 23 days under the conditions observed in Ceará, Brazil. During this process, the main morphological changes associated with growth occur from 14 to 17 days after anthesis (DAA), while the main physiological changes associated with maturation occur after 14 DAA such as softening and color development, evidence of physiological maturity. In experiment 2, it is highlighted that there was a reduction (60 %) in the total vitamin C of '‘Flor-branca’' in the development, being 96 % found in its reduced form, because of a strong activity of ascorbate oxidase (AO) and by stimulating vitamin C biosynthesis and recycling pathways. However, gene expression data show that there may be a post-transcriptional regulatory mechanism that influences the stability and functionality of enzymes. The AO2 isoform is responsible for the degradation of vit. C during ripening. The high content of vit. C in the early stages may be associated with AsA transport. A conclusion was lacking.